2021
DOI: 10.1029/2020ea001518
|View full text |Cite
|
Sign up to set email alerts
|

Appraising the Potential of Using Satellite‐Based Rainfall Estimates for Evaluating Extreme Precipitation: A Case Study of August 2014 Event Across the West Rapti River Basin, Nepal

Abstract:  We set up a rainfall-runoff model using hourly rainfall data and validated it against the hourly water level for the West Rapti River Basin, Nepal. We evaluated the performance of different satellite-based rainfall estimates in capturing an extreme precipitation event. We corrected poor-performed products with respect to gauge data and filled gauge data gaps using the information of other well-performed products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
2
1
0
Order By: Relevance
“…In contrast, precipitation observations serve as the primary input data required for SM modeling. However, all other products were inappropriate with respect to spatial and temporal variation of precipitation over the study area, with similar outcomes found in the previous findings of certain studies [37][38][39]. The temporal estimations of SM2Rain were in better agreement with gauge estimation, which is consistent with the findings of a particular study [10,24].…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, precipitation observations serve as the primary input data required for SM modeling. However, all other products were inappropriate with respect to spatial and temporal variation of precipitation over the study area, with similar outcomes found in the previous findings of certain studies [37][38][39]. The temporal estimations of SM2Rain were in better agreement with gauge estimation, which is consistent with the findings of a particular study [10,24].…”
Section: Discussionsupporting
confidence: 89%
“…Merapi area is IMERG-L. This result is also supported by Talchabhadel et al (2021) who examined the ability of several rain satellites to evaluate extreme rainfall in Nepal and found IMERG-LATE to be the best.…”
Section: Discussionsupporting
confidence: 56%
“…Omranian et al [22] investigated and analyzed the spatiotemporal performance of IMERG-Final for precipitation monitoring during hurricane events, and the findings indicate that the general performance of IMERG-Final is satisfactory in detecting the spatial variability for this heavy rainfall event. Talchabhadel et al [23] evaluated the performance of different satellite rainfall products in capturing extreme precipitation events in the West Rapti River (WRR) basin of Nepal in August 2014. Aiming at the Beijing extreme heavy rainfall event of 21 July 2012, Huang et al [24] reported the performance of the TMPA precipitation products (3B42RT and 3B42V7) in this extreme precipitation event.…”
Section: Introductionmentioning
confidence: 99%